FROM WORKER TO BUSINESS OWNER: UNDERSTANDING CHALLENGES FACING SMALL BUSINESS AMIDST COVID-19 OUTBREAKS - Trianasari, Nana (Jurnal Magister Manajemen, 2021)
TThe Covid-19 pandemic has caused the unprecedented impacts to almost all aspects of human live globally. Travelling and tourism activities are among the most devastating sectors. Being one of the worldly known tourist destinations where over 80% of the local people rely on the tourism sector, Bali is particular case during this Covid-1 outbreak. People who work in the tourism field has been pushed to transform their job in order to survive. Addressing the research gaps, this paper reports the findings of a study that aimed to explore the challenges among hotel/tourism workers in Bali in running small business amidst Covid-19 pandemic. Data were collected from 16 participants using semi structure interview and were analyzed using a qualitative approach. The study revealed four categories representing the challenges of business owner which are lack of management skills, insufficient funding and facilities; lack of creativity and innovation; and lack of experiences. Further discussion, implication, limitation and future research direction are presented.